Soft robots for healthcare applications : design, modelling, and control - Xie, Shane; Zhang, M.; Meng, Wei (Of University of Auckland. Department of Mechanical Engineering) (Healthcare technologies series, 2017)
Robot-assisted healthcare offers benefits for repetitive, intensive and task specific training compared to traditional manual manipulation performed by physiotherapists. However, a majority of existing rehabilitation devices use rigid actuators such as electric motors or hydraulic cylinders which cannot guarantee the safety of patients; novel soft robots combining soft and compliant actuators with stiff skeletons offer a better alternative. This book focuses on the development of these soft robotics for rehabilitation purposes. Topics covered include an introduction to soft robots and the state of the art of their use in healthcare; concept and modelling of a soft rehabilitation actuator - the Peano muscle; design of the reactive Peano muscle; soft wrist rehabilitation robot; development and control of a soft ankle rehabilitation robot (SARR); design, modelling and control strategies of a gait rehabilitation exoskeleton (GAREX); and conclusions and future work. This book presents novel applications of mechatronics to provide better clinical rehabilitation services and new insights into emerging technologies utilized in soft robots for healthcare, and is essential reading for researchers and students working in these and related fields.